2023
DOI: 10.1155/2023/4424718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Limitations in the Management of HBV Patients Attending Clinic at a District Hospital in Ghana

Abstract: Background. Chronic hepatitis B (CHB) is estimated to cause between 500,000 and 1.2 million deaths worldwide every year through cirrhosis and hepatocellular carcinoma (HCC). Liver cirrhosis and HCC are the commonest liver diseases causing death in Ghana. The most critical problem in the management of CHB in sub-Saharan Africa is the high cost of investigations and antiviral drugs. There is scanty information concerning newly diagnosed CHB patients and their management challenges in Ghana. This study sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The situation in Ghana is similar, according to the Polaris Observatory Network, as at 2022 Ghana had a CHB population of 2,769,000, of which only 0.7% had been diagnosed (Polaris Observatory Collaborators et al, 2023). Most HBV patients in Ghana and most African countries would remain undiagnosed because CHB is mostly asymptomatic and patients would usually present late to the hospital CHB complications arise (Duah & Nartey, 2023; Spearman et al, 2023). In Ghana, HBV screening is usually undertaken at health facilities, mostly based on risk assessment and supplemented by community-based testing undertaken by non-governmental organisations (Nartey et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation in Ghana is similar, according to the Polaris Observatory Network, as at 2022 Ghana had a CHB population of 2,769,000, of which only 0.7% had been diagnosed (Polaris Observatory Collaborators et al, 2023). Most HBV patients in Ghana and most African countries would remain undiagnosed because CHB is mostly asymptomatic and patients would usually present late to the hospital CHB complications arise (Duah & Nartey, 2023; Spearman et al, 2023). In Ghana, HBV screening is usually undertaken at health facilities, mostly based on risk assessment and supplemented by community-based testing undertaken by non-governmental organisations (Nartey et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Ghanaian treatment guideline developed in 2014 stipulates treatment for all patients with HBV-related cirrhosis and fibrosis (APRI > 2) with detectable viraemia and chronic active hepatitis, that is persistently elevated ALT (> 2x ULN) (ULN not defined) and viraemia of ≥ 20,000 IU/ irrespective of HBeAg status. However, A recent study at a primary health centre in the Eastern Ghana reported a significant number of patients were unable perform viral load, an essential component in the Ghanaian guideline (Duah & Nartey, 2023). Would the adoption of a simple, yet sensitive guideline like TREAT-B in Ghana, especially at the primary health care level result in reducing the burden of CHB complications?…”
Section: Introductionmentioning
confidence: 99%